Cuerpos extraños en los proventrículos de los bovinos faenados en el camal municipal de Arenillas - Maldonado Erreyes, Jaime Iban (2005)
The present investigation: "Presence of Strange Bodies in the Proventrículos of the Bovine ones", one carries out in the municipal camal of the cantón Arenillas during a period of 13 weeks (14 of sept-14 dic. 2003), with the purpose of identifying the types of bodies strange present and their prevalencia, as well as to determine their relationship with the lesions taken place to the interior of the same ones. During the period of investigation, you inspects a total of 510 animals of which 4 were positive giving a prevalencía of 0.78% as a result and the types of identified strange bodies were: You are founded plastic, be accustomed to, and metal acromizado (needle of sewing). Of the 4 positive cases to alone strange bodies 1 present internal lesion (fibrous fabric) to the interior of the proventrículos.